Human capital and development in the Philippines a festschrift in honor of Alejandro N. Herrin - Capuno, Joseph J.; Orbeta, Aniceto C. Jr. (Makati City Philippine Institute for Development Studies, 2008)
"After many policies have been put in place over the years to uplift the welfare of the Filipinos, the overall human development in the country has not reached its maximum potential. Undoubtedly, much remains to be done, especially in improving the quality of human capital in the Philippines. Policy reforms are needed to improve the access to basic education, provide sufficient work opportunities, strengthen health systems especially in the rural areas, promote child and maternal health and nutrition, and encourage people to practice responsible sexuality and parenthood. The list of gaps can go on, which only reflects the many critical issues that remain unsolved until now. Even how the population should be managed continues to be a controversial, sensitive, and divisive topic. The volume reviews these issues with academic rigor and with an eye toward providing practical policy recommendations. It is a fitting honor to Dr. Alejandro N. Herrin, touted as the "Father of Population and Development" in the Philippines, for his vast research works and institutional capacity-building efforts especially on population management and health issues that have led to many policy initiatives in the country."--Back cover.
Foreword / Josef T. Yap -- Preface / Joseph J. Capuno and Aniceto C. Orbeta, Jr. -- Introduction -- Human capital and development in the Philippines : an appreciation of Dr. Alejandro N. Herrin's opus / Joseph J. Capuno, Aleli D. Kraft, and Aniceto C. Orbeta, Jr. -- Health, education and population : the challenges ahead for the Philippines / Mario Taguiwalo -- Comments / Lorraine Hawkins... et. al -- Population -- Poverty, fertility and family planning practice in the Philippines / Aniceto C. Orbeta, Jr. -- Comments / Winfred Villamil -- Robust determinants of income growth in the Philippines / Dennis S. Mapa, Arsenio M. Balisacan, and Kristine Joy S. Briones -- Comments / Dante Canlas -- Abortion and contraception : their role in explaining Philippine fertility change / Josefina V. Cabigon -- Comments / Aleli D. Kraft -- Session discussion -- Health (1) -- Bargaining for commercial sex / Orville C. Solon -- Comments / Michael M. Alba -- The national health accounts of the Philippines : continuing development and new findings / Rachel H. Racelis... et. al. -- Comments / Marilyn Noval-Gorra -- Health (2) -- Targeting women in urban poor communities for family planning / Alice Joan G. Ferrer -- Comments / Carlo Irwin Panelo -- Health insurance for the poor under decentralization : lessons from the Philippines and Vietnam / Joseph J. Capuno -- Comments / Eduardo Banzon -- Pricing, technology choice, and information in health care markets / Stella A. Quimbo -- Comments / Carlos Antonio Tan, Jr. -- Session discussion -- Development policy -- Governance innovations and gaps in poverty alleviation / Victoria A. Bautista -- Comments / Mario B. Lamberte -- Social theory and urban poverty : implications for research and policy development / Exaltacion Ellevera Lamberte -- Comments / Fernando Aldaba -- Population growth and income : implications on revenue and expenditure of LGUs / Rosemarie G. Edillon and Carlos O. Abad Santos -- Comments / Rosario G. Manasan -- Session discussion -- Households -- Migration and the rural-urban continuum : evidence from Bukidnon, Philippines / Agnes R. Quisumbing and Scott McNiven -- Comments / Leonardo A. Lanzona -- Exploring household saving and consumption-smoothing in the Philippines / Michael M. Alba and Edward C. See -- Comments / Joseph Lim -- A better start in life : evaluation results from an early childhood development program / Socorro A. Gultiano and Elizabeth M. King -- Testimonial in honor of Alejandro N. Herrin -- Testimonials / Ernesto Pernia, Alberto Romualdez, Raul Fabella -- RIMCU at 50 remembers Alex : a tribute / Magdalena C. Cabaraban -- Response from the honoree -- List of contributors, commentators, testimonial presenters, and other participants -- Curriculum vitae of Alejandro N. Herrin.
"Most of the articles in this issue were presented during the Workshop in honor of Professor Alejandro N. Herrin held on 14 August 2006 at the NEDA sa Makati Building in Makati City."--P. xi.
CASM-26666 donated by Prof. John Ponsaran, Php250.00
Keywords: Human capital -- Philippines -- Congresses; Economic development -- Social aspects -- Philippines -- Congresses; Health policy -- Philippines -- Congresses; Philippines -- Population policy -- Congresses; Philippines -- Social policy -- Congresses